Incidence rates of the different initial rhythms during out-of-hospital cardiopulmonary resuscitation and mortality of patients presenting ST elevation myocardial infarction. (3rd May 2023) - Szabo, D; Szabo, A; Magyar, L; Szentgroti, R; Batho, J P; Szegeczky, T; Kocsis, T; Edes, I F; Ruzsa, Z; Becker, D; Merkely, B; Szekely, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Project no. RRF-2.3.1-21-2022-00004 (MILAB) has been implemented with the support provided by the European Union. Development of scientific workshops of medical, health sciences and pharmaceutical educations" Project identification number: EFOP-3.6.3-VEKOP-16-2017-00009. Background: Mortality risk of patients presenting ST-elevation myocardial infarction (STEMI) is extensively researched. On the other hand, the prehospital mortality of them has been studied less frequently. Purpose: We aimed to study the outcomes of STEMI patients with different initial rhythms during cardiopulmonary resuscitation (CPR) using the database of the National Ambulance Service in our country. Methods: We collected data of 632 patients between November 2018 and June 2021 who required CPR because of an out-of-hospital cardiac arrest, and ST elevation was also presented on their ECG before the cardiac arrest or after the return of spontaneous circulation. Primary endpoint was the successful admission to the hospital. Pearson Chi-square test and Mann-Whitney U Test was used for statistical analysis. Results: Of the 632 patients, 102 (16.1%) died before arriving at the hospital. The age of patients survived was median 63 years (IQR 53-70), while the patients died were median 70 years old (IQR 60-77), (p<0.001). The sex rate was non-different, as 33/164 (16.8%) of women and 59/310 (16.0%) of men died out-of-hospital (p=0.815). The CPR initial rhythm was documented in 469 cases (74.2%), the out-of-hospital mortality was 95/469 (20.26%). Of them 73 patients (76.8%) had a non-shockable initial rhythm (pulseless electric activity or asystole, PEA/ASY), and 22 patients (23.2%) died from an initial shockable rhythm (ventricular tachycardia or fibrillation, VT/VF). Patients with an initial VT/VF reached the hospital in 92.5% (273/295), and patients with an initial PEA/ASY survived only in 58% (101/174). (p<0.001) Patients with an initial VT/VF had STEMI anterior in 44.4% (131/295), of them 90.8% (119/131) reached the hospital alive. Patients with an initial VT/VF had STEMI inferior in 41.8% (114/273), of them 97.4% (111/114) were admitted to the hospital alive. (p=0.033) STEMI anterior patients had an initial PEA/ASY in 26% (46/175), while patients with STEMI inferior had an initial non-shockable rhythm in 40.3% (77/191). (p=0.004) Conclusion: Patients with STEMI inferior may have a higher risk for cardiac arrest with a non-shockable rhythm than patients with STEMI anterior. However, patients with STEMI inferior and an initial VT/VF have a higher rate to reach the hospital alive. For individual prediction, more data and complex statistical methods are needed.